Method for improving aging resistance of metal and CFRP laser welding joint and application

By pretreating and microarc oxidizing the metal sheet to form a ceramic oxide film, combined with laser welding and fixing technology, the stability of metal and CFRP joints in an aging environment is solved, and the connection strength and aging resistance are significantly improved. .

CN119187870APending Publication Date: 2024-12-27WENZHOU SPECIAL EQUIP TESTING SCI RES INST (WENZHOU SPECIAL EQUIP EMERGENCY RESPONSE CENT) +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411612315.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The melting point and tissue characteristics of metal and CFRP are quite different. There are limitations in the connection of existing reinforced metal/CFRP welding joints, which leads to the joints being easily broken under load, and the interface temperature field distribution is uneven during welding, which affects the stability of the joints aging. sex.

Method used

By pretreating the metal sheet, including wire cutting, grinding, microarc oxidation and laser welding, a dense ceramic oxide film is formed to improve the connection strength and stability of the metal and CFRP, and a clamp device is used to fix the overlap area to increase pressure. Promote physical adhesion of the molten layer to the metal surface.

Benefits of technology

It significantly improves the aging resistance of metal/CFRP laser welded joints, uniformizes the interface bonding intensity distribution, enhances mechanical locking and chemical bonding, and effectively resists interface failure and air defect problems in aging environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119187870A_ABST
    Figure CN119187870A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the aging resistance of a metal and CFRP laser welding joint and application. The method comprises the following steps that S1, a metal plate is pretreated; s2, performing micro-arc oxidation on the pretreated metal plate sample; s3, lap joint of the metal plate sample and the CFRP plate; s4, laser welding; and S5, cooling for later use. According to the method, the pretreated metal is subjected to micro-arc oxidation treatment, so that a layer of compact oxidation film is formed on the surface of the metal, and then the metal subjected to micro-arc oxidation is singly lapped on the CFRP and is heated by laser, so that the metal is connected with the CFRP, and the ageing resistance of the joint of the metal subjected to micro-arc oxidation and the CFRP is remarkably improved; the method can be widely applied to preparation of metal and nonmetal-based composite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of laser connection of metal and non-metal composite materials, and in particular to a method and application of improving the aging resistance of metal and CFRP laser welding joints. Background Art

[0002] Carbon fiber reinforced thermoplastic resin composites (CFRP) have excellent properties such as high specific strength and high toughness. They are important new lightweight materials and have been gradually widely used in advanced manufacturing in the fields of automobiles, aircraft, spacecraft, construction, industrial equipment, etc. Using CFRP to replace traditional materials in certain parts of structural parts can reduce the weight of the structure while maintaining high performance, reducing energy consumption and costs.

[0003] Since CFRP is prone to stiffness reduction and its own high cost when subjected to complex, huge, and variable loads, it is currently still combined with metal materials to form a multi-material structure. The new problem that arises is how to achieve high-strength connection between CFRP and metal materials. Laser welding has the advantages of simple process, high efficiency, and non-destructiveness, but the melting point and organizational characteristics of metal and CFRP are quite different, and there is a great transition in the microstructure and material properties of the joint interface. This is the difficulty in achieving the welding of the two materials at present, and it is also a huge test for the reliability of the interface bonding under aging environment. The existing method of strengthening the connection of metal / CFRP joints is mainly to obtain an uneven microstructure by pre-treating the metal surface, and apply pressure to the joint during the welding process, so that the CFRP molten resin near the joint interface penetrates into the microstructure of the metal side to form a mechanical anchoring structure, thereby improving the strength of the joint. However, the above method still has limitations. For example, the amount of molten resin may not be enough to completely fill the microstructure of the metal surface, resulting in pores inside the microstructure. These pores not only reduce the actual interface bonding area, but also cause stress concentration. By adding a resin interlayer to the connection interface, the amount of resin at the interface can be effectively increased, which is conducive to promoting the resin to fill the metal surface microstructure and thus inhibit the formation of pores. However, the joint strength is still limited by the strength of the CFRP resin matrix, because under the joint load, the resin that penetrates into the metal surface microstructure acts as a stress concentration point and is also the weakest part of the joint, and the joint is prone to break here. In addition, during the laser welding process, the CFRP melted at the interface needs to be cooled to below the solidification temperature to achieve the combination of the two. During the welding process, the interface temperature field distribution and temperature transient changes are more complex, resulting in uneven interface bonding force. The uneven interface bonding force will have a certain impact on the aging stability of the joint.

[0004] Therefore, a method is needed to break through this limitation, effectively improve the connection strength of metal / CFRP, and improve the mechanical reliability of metal / CFRP joints under long-term engineering application conditions. Summary of the invention

[0005] The problem to be solved by the present invention is that the melting points and organizational characteristics of metal and CFRP are quite different, and there is a great transition in the microstructure and material properties of the joint interface. The existing methods for strengthening the connection of metal / CFRP welding joints still have limitations. For example, when the joint is loaded, the resin that penetrates into the microstructure of the metal surface acts as a stress concentration point and is also the weakest part of the joint, and the joint is prone to breakage here; during the welding process, the interface temperature field distribution and the transient temperature changes are relatively complex, resulting in uneven interface bonding force, which affects the aging stability of the joint.

[0006] In order to solve the above technical problems, the present application provides a method for improving the aging resistance of metal and CFRP laser welding joints, comprising the following steps:

[0007] S1: Pretreatment of metal sheet: Use wire cutting machine to cut metal sheet into metal sheet specimens with the same specifications as CFRP sheet, and process a hole on the width edge of the metal sheet specimen, then grind and flatten the metal sheet specimen, ultrasonically clean, blow dry, and bag for later use;

[0008] S2: Micro-arc oxidation: Prepare a micro-arc oxidation electrolyte, and perform micro-arc oxidation on the metal plate sample under constant voltage mode. After the micro-arc oxidation, wash the metal plate sample with deionized water, then perform ultrasonic cleaning with anhydrous ethanol, and finally use a hair dryer to dry it and bag it for later use;

[0009] S3: Overlap: Place the metal plate sample on the CFRP plate, overlap the non-perforated side of the metal plate sample with the CFRP plate to form an overlap area, and fix the two sides of the overlap area with a clamp device;

[0010] S4: Laser welding: adjust the laser spot position to ensure that the center of the spot and the center line of the overlap area are on the same axis, set the laser welding process parameters, and weld the metal plate sample and the CFRP plate together;

[0011] S5: After welding, the workpiece is cooled to below 50°C at room temperature and unloaded to form a welding joint between the metal plate sample and the CFRP plate.

[0012] According to an embodiment of the present application, the metal sheet is selected from at least one of titanium alloy, stainless steel, aluminum alloy, and magnesium alloy, and the thickness of the metal sheet is 1-5 mm; the CFRP sheet is 20% T300 carbon fiber reinforced PA6 resin.

[0013] According to an embodiment of the present application, step S2 includes the following specific steps:

[0014] S21: Add 80g sodium silicate, 4g sodium fluoride, 8g sodium hydroxide and 8L deionized water into a stainless steel barrel, stir evenly with a glass rod until all dissolved without precipitation, and then let stand for 1h until the electrolyte is stable;

[0015] S22: The electrolysis process parameters are set to a pulse frequency of 100 Hz, a duty cycle of 20%, a voltage of 460 V, and a time of 10 min. During operation, the electrolyte temperature is maintained below 40° C.;

[0016] S23: The metal plate sample is immersed in the electrolyte and fixed by a clamping device. The metal plate sample is connected to the positive electrode of the micro-arc oxidation power supply through an aluminum wire as an anode, and the stainless steel barrel is connected to the negative electrode of the micro-arc oxidation power supply as a cathode. After power is turned on, a ceramic oxide film is formed on the surface of the metal plate sample;

[0017] S24: After the oxidation is completed, the metal plate sample is taken out, washed with deionized water, and then ultrasonically cleaned with anhydrous ethanol for 3 minutes. Finally, it is dried with a hair dryer and bagged for later use.

[0018] According to an embodiment of the present application, the aluminum wire is wrapped in a thermoplastic tube, the aluminum wire passes through the hole and is connected to the metal plate sample, and the thickness of the aluminum wire is adapted to the diameter of the hole.

[0019] According to an embodiment of the present application, the stainless steel barrel is provided with an interlayer, and the interlayer is connected to a cooling water pool through a water pump.

[0020] According to an embodiment of the present application, in step S3, the dimensions of the metal plate sample are 75 mm in length, 30 mm in width, and 2 mm in thickness, the dimensions of the CFRP plate are 75 mm in length, 30 mm in width, and 3 mm in thickness, and the overlapping area is 30 mm×30 mm in size.

[0021] According to an embodiment of the present application, the laser welding process parameters in step S4 are: defocus 0 mm, deflection 2 mm, speed 2 mm / s, and power 320 W-640 W.

[0022] According to an embodiment of the present application, step S1 specifically includes the steps of: polishing the surface of the cut metal plate sample using 320#-2000# SiC sandpaper to remove surface defects, then using anhydrous ethanol ultrasonic cleaning for 3 minutes, and finally blowing the sample dry and bagging it for later use.

[0023] According to an embodiment of the present application, the clamp device includes a fixing plate, which includes a middle transverse groove and raised portions on the upper and lower sides of the groove. A pair of longitudinally parallel pressure rods are assumed above the groove, and the two ends of the pressure rods are slidably installed in the sliding grooves provided on the raised portions; the width of the groove is adapted to the width of the metal sample plate and the CFRP plate; the metal sample plate and the CFRP plate are overlapped up and down and placed in the groove, and a pair of pressure plates slide to both sides of the overlapping area respectively to fix the overlapping area, and the height of the pressure rod is adapted to the height of the overlapping area.

[0024] Another aspect of the present application discloses the use of the above-mentioned method for improving the aging resistance of metal and CFRP laser welding joints in the preparation of metal and non-metallic matrix composite materials.

[0025] The beneficial effects of the technical solution of the present invention compared with the prior art are:

[0026] 1. The method of the present application includes pre-treating the metal surface, micro-arc oxidation the pre-treated metal, forming a dense ceramic oxide film on its surface, and then lap-jointing the micro-arc oxidized metal on the CFRP and heating it with a laser to connect the metal to the CFRP. Then, an aging experiment is performed for comparison. The experimental results show that the aging resistance of the metal and CFRP joint after micro-arc oxidation is significantly improved, because the micro-arc oxidation modified interface significantly refines the peak temperature during welding due to the thermal barrier effect of the ceramic layer, and the width-to-depth ratio of the CFRP melting layer is much higher than that of the unmodified interface, and finally a more uniform interface bonding strength distribution is obtained, and the mechanical stability of the joint is better. At the same time, the mechanical locking enhancement and chemical bond enhancement of the micro-arc oxidation interface can inhibit the aging and shedding expansion of the interface at a microscale, and can more effectively resist the interface failure caused by rapid temperature changes in an aging environment.

[0027] 2. The metal sheet of the present application is subjected to micro-arc oxidation treatment to form a dense oxide film on its surface, which is not affected by the size and depth of the micro-texture on the metal surface. Even under low heat input, this process can still avoid the problem of post-welding air defects.

[0028] 3. Use pressure rods to fix the overlap area. From the perspective of pressure affecting interface heat conduction, the increase in contact pressure can enhance interface heat transfer, promote the physical adhesion between the molten layer and the metal surface, promote the discharge of residual air, improve the interface stress state, and further enhance the bonding strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a flowchart of a method for improving the aging resistance of metal and CFRP laser welding joints according to an example of the present invention;

[0030] Figure 2It is a schematic diagram of the structure of the metal plate sample and the CFRP plate overlapped in the example of the present invention;

[0031] Figure 3 A schematic diagram of the state of the metal plate sample and the CFRP plate when being welded in an example of the present invention;

[0032] Figure 4 A schematic diagram of a unit temperature cross-load cycle in an aging test in an example of the present invention;

[0033] Figure 5 Schematic diagram of the oxidation tensile shear performance results of the micro-arc oxidation aluminum alloy / CFRP welded joint and the aluminum alloy / CFRP welded joint in the examples of the present invention;

[0034] Figure 6 It is a schematic diagram of the mechanical properties change trend results of the micro-arc oxidation aluminum alloy / CFRP welded joint and the aluminum alloy / CFRP welded joint in the examples of the present invention.

[0035] The following are the descriptions of the reference numerals:

[0036] 1. Metal plate specimen, 2. CFRP plate, 3. Laser, 10. Fixing plate, 11. Groove, 12. Raised part, 13. Pressure rod, 131. Slide groove, A. Micro-arc oxidation aluminum alloy / CFRP welded joint, B. Aluminum alloy / CFRP welded joint.

[0037] in Figure 3 The arrow in the figure indicates the welding direction. DETAILED DESCRIPTION

[0038] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. The following embodiments are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0039] See also Figures 1 to 4 A method for improving the aging resistance of a metal and CFRP laser welded joint is shown, comprising the following steps:

[0040] S1: Pretreatment of the metal sheet: Use a wire cutting machine to cut the metal sheet into a metal sheet sample 1 with the same specifications as the CFRP sheet 2, and process a hole on the width edge of the metal sheet sample 1, then grind and flatten the metal sheet sample 1, ultrasonically clean it, blow dry it, and bag it for later use;

[0041] The purpose of step S1 is to clean the metal plate sample 1 to remove surface impurities and oxide film.

[0042] Specifically, the metal plate is selected from at least one of titanium alloy, stainless steel, aluminum alloy and magnesium alloy, and the thickness of the metal plate is 1-5 mm; the CFRP plate 2 is preferably 20% T300 carbon fiber reinforced PA6 resin.

[0043] Specifically, step S1 also includes the following steps: using 320#-2000# SiC sandpaper to grind the surface of the cut metal plate sample 1 to make it smooth to remove surface defects, then using anhydrous ethanol to ultrasonically clean it for 3 minutes, and finally blowing the sample dry and bagging it for later use.

[0044] S2: Micro-arc oxidation: Prepare a micro-arc oxidation electrolyte, and perform micro-arc oxidation on the metal plate sample 1 under a constant voltage mode. After the micro-arc oxidation is completed, the metal plate sample 1 is first washed with deionized water, then ultrasonically cleaned, blown dry, and then bagged for later use;

[0045] Specifically, step S2 includes the following specific steps:

[0046] S21: First, prepare the required micro-arc oxidation electrolyte. The electrolyte is a Na2SiO3 system with a specific formula ratio of Na2SiO3:NaF:NaOH (20:1:2). Specifically, add 80g of sodium silicate, 4g of sodium fluoride, 8g of sodium hydroxide and 8L of deionized water into a stainless steel barrel, stir evenly with a glass rod until all dissolved without precipitation, and then let it stand for 1h until the electrolyte is stable;

[0047] S22: After the micro-arc oxidation electrolyte is configured, the electrolysis process parameters are set, and the electrolysis process parameters are set to a pulse frequency of 100 Hz, a duty cycle of 20%, a voltage of 460 V, and a time of 10 min. During operation, the electrolyte temperature is maintained below 40° C.;

[0048] S23: The metal plate sample 1 is immersed in the electrolyte and fixed by a clamping device. The metal plate sample 1 is connected to the positive electrode of the micro-arc oxidation power supply through an aluminum wire as an anode, and the stainless steel barrel is connected to the negative electrode of the micro-arc oxidation power supply as a cathode. After power is turned on, a ceramic oxide film is formed on the surface of the metal plate sample 1;

[0049] S24: After the oxidation is completed, the metal plate sample 1 is taken out, first washed with deionized water, then ultrasonically cleaned with anhydrous ethanol for 3 minutes, and finally dried with a hair dryer and bagged for later use.

[0050] Specifically, the aluminum wire is wrapped with a thermoplastic tube, and the aluminum wire passes through the hole to be connected to the metal plate sample 1, and the thickness of the aluminum wire is adapted to the diameter of the hole.

[0051] Furthermore, the stainless steel barrel containing the electrolyte is provided with an interlayer, which is connected to a cooling water pool through a water pump, so that cooling water circulates during the experiment and keeps the electrolyte temperature below 40°C.

[0052] S3: Overlap: Figure 2As shown, a metal plate sample 1 is placed on a CFRP plate 2, and the non-perforated side of the metal plate sample 1 is overlapped with the CFRP plate 2 to form an overlap area, and both sides of the overlap area are fixed by a clamp device;

[0053] Specifically, Figure 3 As shown, the clamp device includes a fixing plate 10, and the fixing plate 10 includes a middle transverse groove 11 and raised portions 12 on the upper and lower sides of the groove 11. A pair of longitudinally parallel pressure rods 13 are assumed to be provided above the groove 11, and the two ends of the pressure rods 13 are slidably installed in the slide grooves 131 provided on the raised portions 12; the width of the groove 11 is adapted to the width of the metal sample plate and the CFRP plate 2; the metal sample plate and the CFRP plate 2 are overlapped up and down and placed in the groove 11, and a pair of pressure plates slide to the two sides of the overlapping area respectively to fix the overlapping area, and the height of the pressure rod 13 is adapted to the height of the overlapping area.

[0054] Specifically, in step S3, the dimensions of the metal plate sample 1 are 75 mm in length, 30 mm in width, and 2 mm in thickness, the dimensions of the CFRP plate 2 are 75 mm in length, 30 mm in width, and 3 mm in thickness, and the overlapping area has an area of ​​30 mm×30 mm.

[0055] Furthermore, the width of the pressure rod 13 may be 2 mm.

[0056] S4: Laser welding: adjust the laser spot position to ensure that the center of the spot and the center line of the overlap area are on the same axis, set the laser welding process parameters, and weld the metal plate sample 1 and the CFRP plate 2 together;

[0057] Specifically, the laser welding process parameters in step S4 are: defocus 0 mm, deflection 2 mm, speed 2 mm / s, power 320 W-640 W.

[0058] S5: After welding, the workpiece is cooled to below 50° C. at room temperature and then unloaded to form a welding joint between the metal plate sample 1 and the CFRP plate 2.

[0059] Another aspect of the present application discloses the application of the method for improving the aging resistance of metal and CFRP laser welded joints in the preparation of metal and non-metallic matrix composite materials.

[0060] Example 1: Welding of aluminum alloy sheet without micro-arc oxidation and CFRP sheet 2

[0061] Step 1: Use a wire cutting machine to cut the 800×300×2mm 5052 aluminum alloy plate into samples with a size of 75×30×2mm.

[0062] Step 2: Use 320#~2000# SiC sandpaper to smooth the surface of the cut sample and remove surface defects. Then use anhydrous ethanol to ultrasonically clean for 3 minutes, and finally blow dry the sample and bag it for later use.

[0063] Step 3: The CFRP plate 2 is made of 20% T300 carbon fiber reinforced PA6 resin and has a size of 75mm×30mm×2mm. The pretreated aluminum alloy plate is placed on the CFRP plate 2 and put into the groove 11 of the fixing plate 10 for overlap. The overlapping area is 30mm*30mm. The two sides of the overlapping area are fixed by a pair of pressure rods 13 provided on the fixing plate 10.

[0064] Step 4: The parameters of the laser connection process are set to defocus 0mm, deflection 2mm, speed 2mm / s and power 600w. Start the welding equipment and perform overlap welding on the overlap area. After welding, use a handheld thermometer to measure the surface temperature of the aluminum alloy. After cooling to below 50°C, unload the fixture to avoid unstable connection due to material shrinkage during the cooling process, and obtain the aluminum alloy / CFRP joint sample.

[0065] Step 5: Place the aluminum alloy / CFRP joint sample obtained in step 4 into the Xe-3IIBSE xenon lamp aging test chamber, which can simulate natural full-band light. The temperature alternation range is the black standard temperature of 20℃-60℃, and the aging test is carried out for 0 (unaged), 48, 96, 144, 192 and 240 hours. The specific experimental parameters and cyclic loading conditions are set as follows: the test environment is room temperature 22℃; Figure 4 As shown in the figure, the temperature alternation range is the black mark temperature of 20℃-60℃, the temperature is increased from 20℃ to 60℃, the heating time is 5min, and the temperature is kept for 10min; then it is reduced from 60℃ to 20℃, the cooling time is 5min, and the temperature is kept for 10min. It takes 30min to complete a unit temperature alternation cycle; the irradiance is set to 0.5W / (m 2 ·nm), in a unit temperature load cycle, turn on the light when heating and keeping warm to simulate the light condition, turn off the light when cooling to simulate the dark condition; every four unit temperature load cycles are one cycle, add a spray cycle in each cycle, the humidity condition is 90% during the spray, and the spray is turned off in the remaining cycles to maintain the humidity condition of 50%. After the aging test, the aluminum alloy / CFRP joint sample is placed in the test environment again until it reaches room temperature, and then the mechanical properties test is carried out.

[0066] Step 6: Perform mechanical property tests on aluminum alloy / CFRP joint specimens at various aging nodes to obtain tensile shear performance results and mechanical property change trend results as shown in the figure below: Figure 5 and Figure 6 shown.

[0067] Example 2: Welding of micro-arc oxidation aluminum alloy plate and CFRP plate 2

[0068] Step 1: Use a wire cutting machine to cut the 800×300×2mm 5052 aluminum alloy plate into samples with a size of 75×30×2mm. In order to facilitate the preparation of subsequent micro-arc oxidation samples, a hole with a diameter of 2mm is processed on the width edge of the cut aluminum alloy sample.

[0069] Step 2: Use 320#-2000# SiC sandpaper to smooth the surface of the processed aluminum alloy sample and remove surface defects. Then use anhydrous ethanol to ultrasonically clean for 3 minutes, and finally blow dry the sample and bag it for later use.

[0070] Step 3: Prepare the micro-arc oxidation electrolyte, the electrolyte is a Na2SiO3 system, and its specific formula ratio is Na2SiO3:NaF:NaOH (20:1:2). A stainless steel barrel is used as an electrolytic cell to carry the electrolyte. 80g of sodium silicate, 4g of sodium fluoride and 8g of sodium hydroxide are added to 8L of deionized water, and stirred evenly with a glass rod until all are dissolved without precipitation, and then allowed to stand for 1h until the electrolyte is stable; an aluminum alloy sample is placed in the electrolyte and fixed with a clamping device, a 2mm aluminum wire passes through the holes of the aluminum alloy sample and is connected to the positive electrode of the micro-arc oxidation power supply. The aluminum alloy sample serves as the anode in the experiment, and the stainless steel barrel is connected to the negative electrode of the power supply and serves as the cathode in the experiment; the specific parameters of the micro-arc oxidation are set as: a pulse frequency of 100Hz, a duty cycle of 20%, a voltage of 460V, and a time of 10min. At the same time, the interlayer of the electrolytic cell is connected to a cooling water pool. During the experiment, the cooling water circulates and keeps the electrolyte temperature below 40°C; after the preparation is completed, the aluminum alloy sample is taken out, washed with deionized water, and then ultrasonically cleaned with anhydrous ethanol for 3min, and finally dried with a hair dryer and bagged for use.

[0071] The aluminum wire is wrapped with a thermoplastic tube to avoid micro-arc oxidation reaction that affects the stability of the sample coating.

[0072] Step 6: Laser weld the micro-arc oxidized aluminum alloy sample obtained in step 3 with CFRP: CFRP uses 20% T300 carbon fiber reinforced PA6 resin, and the micro-arc oxidized aluminum alloy sample overlaps the non-perforated side with CFRP to avoid structural defects in the welded joint. The overlap size is 30mm×30mm; Figure 3As shown, this experiment adopts laser 3 straight line welding method, the length of laser 3 straight line path is 24mm, the welding position is the center line of the overlap area, parallel to the width direction of the aluminum alloy sample, the laser welding process parameters are set to defocus 0mm, deflection 2mm, speed 2mm / s, power 600w, and 98% argon + 2% nitrogen shielding gas is used for protection during welding, and the shielding gas flow rate is constant at 1L / min; after welding, a handheld thermometer is used to measure the surface temperature of the aluminum alloy, and the fixture is unloaded when it is cooled to below 50°C to avoid unstable connection due to material shrinkage during cooling, and obtain a micro-arc oxidation aluminum alloy / CFRP joint sample.

[0073] Step seven, place the micro-arc oxidation aluminum alloy / CFRP joint sample in step six into the Xe-3IIBSE xenon lamp aging test chamber, which can simulate natural full-band light. The temperature alternation range is the black standard temperature of 20℃~60℃, and aging tests are carried out for 0 (unaged), 48, 96, 144, 192 and 240 hours. The specific experimental parameters and cyclic loading conditions are set as follows: the test environment is room temperature 22℃; the temperature alternation range is the black standard temperature of 20℃-60℃, the temperature is increased from 20℃ to 60℃, the heating time is 5min, and the temperature is kept at room temperature for 10min; then it is reduced from 60℃ to 20℃, the cooling time is 5min, and the temperature is kept at room temperature for 10min. It takes 30min to complete a unit temperature loading cycle; the irradiance is set to 0.5W / (m 2 ·nm), in a unit temperature load cycle, turn on the light when heating and keeping warm to simulate the light condition, turn off the light when cooling to simulate the dark condition; every four unit temperature load cycles are one cycle, add a spray cycle in each cycle, the humidity condition is 90% during the spray, and the spray is turned off in the remaining cycles to maintain the humidity condition of 50%. After the aging test, place it in the test environment until it reaches room temperature, and then conduct the mechanical properties test.

[0074] Step 8: The mechanical properties of the micro-oxygen arc-treated aluminum alloy / CFRP joint specimens were tested at various aging nodes to obtain the tensile shear performance results and mechanical properties change trend results as shown in the figure. Figure 5 and Figure 6 shown.

[0075] From the above, we can see that in the mechanical properties test, Figure 5 The tensile shear performance results show that the maximum force of the micro-oxygen arc aluminum alloy / CFRP joint is significantly better than that of the aluminum alloy / CFRP joint in the initial condition. As the aging time changes, the maximum force of the aluminum alloy / CFRP joint shows a downward trend, while the maximum force of the micro-oxygen arc aluminum alloy / CFRP joint does not change significantly. Figure 6The results of the mechanical property change trend show that with the change of aging time cycle, the percentage of mechanical properties of aluminum alloy / CFRP joints treated with micro-oxygen arc treatment does not change much, approaching a straight line, but the percentage of mechanical properties of aluminum alloy / CFRP joints without micro-oxygen arc treatment shows a significant downward trend. It can be seen that the aging resistance of the welded joints of metal and CFRP after micro-oxidation is significantly improved.

[0076] In summary, the technical solution of the present invention has the following beneficial effects:

[0077] 1. The method of the present application includes pre-treating the metal surface, micro-arc oxidation the pre-treated metal, forming a dense ceramic oxide film on its surface, and then lap-jointing the micro-arc oxidized metal on the CFRP and heating it with a laser to connect the metal to the CFRP. Then, an aging experiment is performed for comparison. The experimental results show that the aging resistance of the metal and CFRP joint after micro-arc oxidation is significantly improved, because the micro-arc oxidation modified interface significantly refines the peak temperature during welding due to the thermal barrier effect of the ceramic layer, and the width-to-depth ratio of the CFRP melting layer is much higher than that of the unmodified interface, and finally a more uniform interface bonding strength distribution is obtained, and the mechanical stability of the joint is better. At the same time, the mechanical locking enhancement and chemical bond enhancement of the micro-arc oxidation interface can inhibit the aging and shedding expansion of the interface at a microscale, and can more effectively resist the interface failure caused by rapid temperature changes in an aging environment.

[0078] 2. The metal sheet of the present application is subjected to micro-arc oxidation treatment to form a dense oxide film on its surface, which is not affected by the size and depth of the micro-texture on the metal surface. Even under low heat input, this process can still avoid the problem of post-welding air defects.

[0079] 3. Use pressure rods to fix the overlap area. From the perspective of pressure affecting interface heat conduction, the increase in contact pressure can enhance interface heat transfer, promote the physical adhesion between the molten layer and the metal surface, promote the discharge of residual air, improve the interface stress state, and further enhance the bonding strength.

[0080] The above are only preferred embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the description and illustrations of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for improving the aging resistance of metal and CFRP laser welding joints, characterized in that: The following steps are involved: S1: Pretreatment of metal sheet: Use a wire cutting machine to cut the metal sheet into metal sheet samples with the same specifications as the CFRP sheet, and process a hole on the width edge of the metal sheet sample, then grind and flatten the metal sheet sample, ultrasonically clean it, blow dry it, and bag it for later use; S2: Micro-arc oxidation: prepare a micro-arc oxidation electrolyte, and perform micro-arc oxidation on the metal plate sample under a constant voltage mode. After the micro-arc oxidation, the metal plate sample is first washed with deionized water, then ultrasonically cleaned with anhydrous ethanol, and finally dried with a hair dryer and bagged for later use; S3: overlapping: placing the metal plate sample on the CFRP plate, overlapping the non-perforated side of the metal plate sample with the CFRP plate to form an overlapping area, and fixing the two sides of the overlapping area with a clamp device; S4: Laser welding: adjust the laser spot position to ensure that the center of the laser spot and the center line of the overlap area are on the same axis, set the laser welding process parameters, and weld the metal plate sample and the CFRP plate together; S5: After welding, the workpiece is placed at room temperature and cooled to below 50° C. for unloading to form a welding joint between the metal plate sample and the CFRP plate.

2. The method for improving the aging resistance of metal and CFRP laser welding joints according to claim 1, characterized in that: The metal plate is selected from at least one of titanium alloy, stainless steel, aluminum alloy and magnesium alloy, and the thickness of the metal plate is 1-5 mm; the CFRP plate is 20% T300 carbon fiber reinforced PA6 resin.

3. The method for improving the aging resistance of metal and CFRP laser welding joints according to claim 1, characterized in that: The step S2 comprises the following specific steps: S21: Add 80g sodium silicate, 4g sodium fluoride, 8g sodium hydroxide and 8L deionized water into a stainless steel barrel, stir evenly with a glass rod until all dissolved without precipitation, and then let stand for 1h until the electrolyte is stable; S22: The electrolysis process parameters are set to a pulse frequency of 100 Hz, a duty cycle of 20%, a voltage of 460 V, and a time of 10 min. During operation, the electrolyte temperature is maintained below 40° C.; S23: The metal plate sample is immersed in the electrolyte and fixed by a clamping device. The metal plate sample is connected to the positive electrode of the micro-arc oxidation power supply through an aluminum wire as an anode, and the stainless steel barrel is connected to the negative electrode of the micro-arc oxidation power supply as a cathode. After power is turned on, a ceramic oxide film is formed on the surface of the metal plate sample; S24: After the oxidation is completed, the metal plate sample is taken out, first washed with deionized water, then ultrasonically cleaned with anhydrous ethanol for 3 minutes, and finally dried with a hair dryer and bagged for later use.

4. The method for improving the aging resistance of metal and CFRP laser welding joints according to claim 3 is characterized in that: The aluminum wire is wrapped with a thermoplastic tube, passes through the hole and is connected to the metal plate sample, and the thickness of the aluminum wire is adapted to the diameter of the hole.

5. The method for improving the aging resistance of metal and CFRP laser welding joints according to claim 3, characterized in that: The stainless steel barrel is provided with an interlayer, and the interlayer is connected to a cooling water pool through a water pump.

6. The method for improving the aging resistance of metal and CFRP laser welding joints according to claim 1, characterized in that: In step S3, the size of the metal plate sample is 75 mm in length, 30 mm in width, and 2 mm in thickness; the size of the CFRP plate is 75 mm in length, 30 mm in width, and 3 mm in thickness; and the size of the overlap area is 30 mm×30 mm.

7. The method for improving the aging resistance of metal and CFRP laser welding joints according to claim 1, characterized in that: The laser welding process parameters in step S4 are: defocus 0 mm, deflection 2 mm, speed 2 mm / s, power 320 W-640 W.

8. The method for improving the aging resistance of metal and CFRP laser welding joints according to claim 1, characterized in that: The step S1 specifically includes the steps of: using 320#-2000# SiC sandpaper to smooth the surface of the cut metal plate sample to remove surface defects, then using anhydrous ethanol to ultrasonically clean for 3 minutes, and finally blowing the sample dry and bagging it for later use.

9. The method for improving the aging resistance of metal and CFRP laser welding joints according to claim 1, characterized in that: The clamp device includes a fixing plate, which includes a horizontal groove in the middle and raised parts on the upper and lower sides of the groove. A pair of longitudinally parallel pressure rods are assumed to be provided above the groove, and the two ends of the pressure rods are slidably installed in the sliding grooves provided on the raised parts; the width of the groove is adapted to the width of the metal sample plate and the CFRP plate; the metal sample plate and the CFRP plate are overlapped up and down and placed in the groove, and a pair of the pressure plates slide to the two sides of the overlapping area respectively to fix the overlapping area, and the height of the pressure rod is adapted to the height of the overlapping area.

10. Use of the method for improving the aging resistance of metal and CFRP laser welded joints according to any one of claims 1 to 9 in the preparation of metal and non-metallic matrix composite materials.